Pseudopapillary and Macrofollicular Microscopic Growth Patterns in an Advanced Stage Ovarian Dysgerminoma: A Case Report - Fatemeh Nili; Niusha Noubari; Alireza Abdollahi (Iranian Society of Pathology, 2018)
ysgerminoma is one of the two most common types of ovarian germ cell tumors. Providing accurate pathologic diagnosis and treatment planning, the prognosis is good even in advanced stages. Pathologic diagnosis is generally straightforward. In microscopic examination, the usual known growth patterns in tumor cells are solid, trabecular, insular and rarely pseudoglandular. In this paper, we reported an advanced ovarian dysgerminoma with different microscopic patterns of growth, including pseudopapillary and macrofollicular structures, in an 18-year-old woman. The patient underwent staging laparotomy and is currently receiving chemotherapy.